2016
DOI: 10.1093/brain/aww199
|View full text |Cite
|
Sign up to set email alerts
|

Delayed seizures after intracerebral haemorrhage

Abstract: Late seizures after intracerebral haemorrhage occur after the initial acute haemorrhagic insult subsides, and represent one of its most feared long-term sequelae. Both susceptibility to late seizures and their functional impact remain poorly characterized. We sought to: (i) compare patients with new-onset late seizures (i.e. delayed seizures), with those who experienced a recurrent late seizure following an immediately post-haemorrhagic seizure; and (ii) investigate the effect of late seizures on long-term fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 34 publications
2
57
1
Order By: Relevance
“…Age has been previously evaluated as a risk factor for the development of post-stroke seizures with conflicting results. 2, 3, 7, 8, 12, 13, 16 In this study, we found that younger age was strongly associated with an increased relative risk of development of seizures after stroke. In addition, we found that non-white race was associated with the development of post-stroke seizures in the multi-state analysis, but not in the Medicare claims analysis where all patients were ≥66 years of age.…”
Section: Discussionsupporting
confidence: 48%
“…Age has been previously evaluated as a risk factor for the development of post-stroke seizures with conflicting results. 2, 3, 7, 8, 12, 13, 16 In this study, we found that younger age was strongly associated with an increased relative risk of development of seizures after stroke. In addition, we found that non-white race was associated with the development of post-stroke seizures in the multi-state analysis, but not in the Medicare claims analysis where all patients were ≥66 years of age.…”
Section: Discussionsupporting
confidence: 48%
“…Patients with ICH were followed from the index date until PSE development, three years after the index date, death, withdrawal from the health insurance program, or the end of data available period (31 December 2013), whichever occurred first. Since PSE tends to develop within 3 years after stroke , patients were followed for a maximum period of 3 years to minimize the likelihood of including epilepsy caused by other factors such as brain tumour and head injury .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, ion dyshomeostasis is present for at least two weeks after collagenase ICH, giving a large therapeutic window in which bumetanide could theoretically provide benefit [2]. In patients, there is also a large therapeutic window in which electrical imbalances can be addressed, with post-ICH seizures occurring from onset until months after the stroke [27,28]. It should be noted that seizures were not observed in the whole blood model of ICH [16], but they do occur in the collagenase model [16,29].…”
Section: Introductionmentioning
confidence: 99%